Exploring the cultural competence of undergraduate nursing students in Saudi Arabia. (March 2018) - Halabi, Jehad O.; de Beer, Jennifer
Abstract: Purpose: To explore the cultural competence of undergraduate nursing students at a college of nursing, Saudi Arabia. Design: A descriptive exploratory design was used to explore the Saudi undergraduate nursing students' level of cultural competency. Method: The convenience sample included 205 nursing students affiliated with a college of nursing at a health science university in Jeddah, Saudi Arabia. Data was collected using the Inventory for Assessing the Process of Cultural Competence-Revised (IAPCC-R) consisting of 25 items. The tool reported acceptable reliability of Cronbach alpha 0.89. Results: The majority of students were culturally aware and dealt with people from different cultures. One-third preferred to have training on culture over a period of time. Half the students preferred studying a special course related to working with people from different cultures. Cultural desire reported the highest mean while cultural knowledge scored the lowest among the cultural competence subscales despite students being exposed to some cultural knowledge content in their training. Conclusions: Implementing the guidelines for culturally competent care assure covering all aspects of care with consideration of cultural heritage as a main concept. Comparative study of nurses' and students' perception is further recommended. Highlights: Nursing students are more culturally aware than culturally competent. Cultural competence is increased by previous knowledge and exposure to other cultures. Junior students were more culturally knowledgeable. Nursing students are motivated and willing to learn about other cultures.